Menggunakan Media Pembelajaran Quizizz Dalam Meningkatkan Motivasi Belajar Peserta Didik Pada Pembelajaran Dasar-Dasar Manajemen Perkantoran: Using Quizizz Learning Media to Increase Students' Learning Motivation in Learning the Basics of Office Management - Syahruni R, Nur; Darwis, Muh.; Hajrah, Sitti (Jurnal Education, 2025)
Through a Classroom Action Research (CAR) approach, this study aims to optimize students' intrinsic motivation in the learning process by integrating the interactive Quizizz platform as an innovative learning media. The research subjects include all 10th-grade students majoring in Office Management and Business Services at SMK Negeri 1 Makassar in the 2024/2025 academic year, involving 35 students consisting of 6 males and 29 females. The primary focus of this research is the internal drive that motivates students to actively engage in learning the Office Fundamentals course. Aspects examined include students' enthusiasm for participating in the learning process, their perseverance in completing complex tasks, and their level of participation and commitment to academic responsibilities. The primary data collection tools in this study are field notes or observations and documentation archives. The data analysis used is descriptive numerical, with an emphasis on the calculation of proportions. The research results show that the percentage increase in student motivation from 65% in cycle I to 80% in cycle II, as well as an increase in engagement from 60% to 75%, shows the effectiveness of Quizizz in improving the learning experience.